Adverse childhood experiences and repetitive negative thinking in adulthood: A systematic review. (16th April 2021) - Mansueto, Giovanni; Cavallo, Chiara; Palmieri, Sara; Ruggiero, Giovanni Maria; Sassaroli, Sandra; Caselli, Gabriele
Abstract: Background: It has been proposed that repetitive negative thinking (worry and rumination) may be more common among adults who have been exposed to childhood adverse experiences, leading to emotional disorders and other adverse outcomes. The current study aims to present a comprehensive evaluation of the literature examining the relationship between the exposure to childhood adversities, repetitive negative thinking and clinical outcomes in adulthood. Methods: In accordance with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) criteria, a search was conducted on PubMed and Ebsco. A manual search of reference lists was also run. Search terms were 'childhood adversity/childhood abuse/childhood neglect/early loss event AND worry or rumination'. Results: A total of 18 studies met the inclusion criteria. In both non‐clinical and clinical populations, worry and rumination seem to be common among adults exposed to childhood abuse or childhood neglect. Among adults who have been exposed to childhood adversities, rumination seems to be associated with worse clinical outcomes such as severe psychiatric symptoms, depression, dysphoria, suicidal ideation, cognitive complaints, post‐traumatic stress symptoms and aggression. Conclusion: Early experiences of abuse and neglect may be associated with a tendency to engage in repetitive negative thinking, such as worry and rumination, in adulthood. Among adults, with a history of childhood adversities, tailored treatment to reduce repetitive negative thinking should be considered.